Analysis of Gas Utilization Rate of Vanadium Titanium Magnetite Reduced by CH4-H2-CO Mixed Gas in Blast Furnace - Xudong Gao; Xin Li (Archives of Metallurgy and Materials, 2025)
Gas utilization rate is a very important production parameter in the ironmaking blast furnace (BF), which can effectively reflect the utilization of fuel chemical energy. While hydrogen rich gas (such as shale gas) was injected into BF, with the introduction of CH4 in the hydrogen rich gas, the traditional calculation formula for the utilization rate of binary mixed gas (H2-CO) was no longer suitable for the calculation of the utilization rate of ternary mixed gas (CH4-H2-CO). Based on the principle of oxygen migration in the gas-solid reduction reaction, this paper established and derived the method for calculating the utilization rate of mixed gas after methane-rich gas was injected into BF (the mixed gas changes from H2-CO type to CH4-H2-CO type), it is helpful to analyze the influence of CH4 introduction in hydrogen rich gas on the utilization rate of mixed gas in reduction reaction after injecting hydrogen rich gas. In this paper, the change of gas utilization rates and physical phases of 0.5 mol Fe2O3, 0.5 mol V2O5 and 1 mol TiO2 reduced by different amounts of H2-CO or CH4-H2-CO at 700℃, 850℃ and 1000℃ were studied respectively, some meaningful results were obtained through comparative analysis, which provides a theoretical basis for methane rich gas injection practice of vanadium titanium magnetite blast furnace (VTM-BF).